In-vitro and in-vivo antimalarial activity of caffeic acid and some of its derivatives. (22nd July 2018) - Alson, Sylvain G; Jansen, Olivia; Cieckiewicz, Ewa; Rakotoarimanana, Hajatiana; Rafatro, Herintsoa; Degotte, Gilles; Francotte, Pierre; Frederich, Michel
Abstract: Objectives: To explore the in-vitro and in-vivo antimalarial potential of caffeic acid and derivatives. Methods: Two common phenolic acids (caffeic acid and chlorogenic acid) were evaluated for in-vitro and in-vivo antiplasmodial activity in comparison with some semi-synthetic derivatives that were synthesized. An in-vitro assay based on plasmodial lactate dehydrogenase activity, and the classical in-vivo 5-day suppressive test from Peters on an artemisinin-resistant Plasmodium berghei strain was used. Parasitic stage sensitivity to ethyl caffeate was determined in this work. Key findings: Phenolic acid esters derivatives showed better antiplasmodial activity than corresponding phenolic acids. The derivative with the highest in-vitro activity being caffeic acid ethyl ester, exhibiting an IC50 = 21.9 ± 9.4 μm . Ethyl caffeate and methyl caffeate were then evaluated for antimalarial activity in vivo and ethyl caffeate showed a growth inhibition of 55% at 100 mg/kg. Finally, it seems that ethyl caffeate blocks the growth of young parasitic forms. Conclusions: Our study provides evidence for an antimalarial potential of caffeic acid derivatives which are common in several medicinal plants traditionally used against malaria. It also demonstrates the possibility to use such derivatives in the treatment of malaria.